Efek Penggunaan Earphone sebagai Faktor Resiko Kejadian Noise Induced Hearing Loss - Eka Susiyanti; Mukhlis Imanto (Majority, 2020)
Noise Induced Hearing Loss (NIHL) is a type of sensorineural deafness type of hearing loss caused by months or years of cumulative exposure to high levels of noise that can cause permanent hearing loss. Noise is a sound that is unwanted and can cause health problems and comfort within a certain period of time. Noise that is 85 decibels (dB) or more can cause damage to Corti's hearing receptors in the inner ear. The use of earphones for a long time and at high volume levels can mediate the increase in damage to hair cell structures such as mitochondria, lysosomes which can cause hearing loss. This is because the noise intensity produced by the earphones is 121 dB with a high volume level and the resulting noise peak can reach 139 dB. Research by Widen et al with a sample of 280 adolescents who listened to music using earphones for 3 hours or more on each occasion per day, 14.0% reported having poor hearing subjectively. Furthermore, 7–8% reported frequent or constant hearing problems, such as tinnitus, voice sensitivity or sound fatigue. The high prevalence of hearing loss in individual earphone users is related to noise intensity, noise frequency, length of time of exposure, noise spectrum, and individual susceptibility factors. Based on the studies that have been done, exposure to noise generated by earphones can increase the risk of hearing loss due to noise or Noise Induced Hearing Loss (NIHL).